Evaluation of communities of birds in secondary forests restored in abandoned paddocks situated along the basin of the Zapotal River, Hojancha Costa Rica - Núñez Guale, M.A. (2008)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2008